I am well aware of it Yet my Students have to Learn in comfort way: Translanguaging as Mediated English Language Pedagogy - Devilito P. Tatipang; Syarifuddin Dollah; Sukardi Weda; Geminastiti Sakkir; Nihta V. F. Liando; Fergina Lengkoan (Journal of English Culture, Language, Literature and Education, 2025)
This study examines the practice of translanguaging in English language learning in one of the secondary schools in Manado which is a multilingual environment with the use of the local language of Manado Indonesian and English The main objective of the study was to understand teachers beliefs and their translanguaging practices as language mediation strategies that support concept understanding social interaction and student motivation The method used was a case study with three English teachers as participants collecting data through interviews observations and documentation then analyzed thematically The findings suggest that translanguaging serves as a cultural and cognitive bridge that facilitates students to understand the material more deeply and strengthen their linguistic identity Despite concerns about reduced exposure to English due to the use of local languages and Indonesian teachers use translanguaging strategically to balance learning The main obstacles found are the limitations of school policies and teacher training that support the implementation of translanguaging In addition translanguaging has been shown to increase students motivation to learn and active participation This research recommends the development of teacher education and training policies that are responsive to language diversity as well as the development of a curriculum that accommodates translanguaging as a legitimate learning strategy This study makes an important contribution to the development of inclusive and contextual English language pedagogy in multilingual classrooms in Indonesia< p>